PID Controller for Vibration Reduction and Performance Improvement of Handheld Tools - Salim, Mohd Azli; Noordin, Aminurrashid; Abdul Munir , Fudhail (IJENS Publishers, 2011)
This paper proposes a PID Controller to mprove handheld tools performance and at the same time reduce vibration occurs during its operation. Two experiments has been setup to record vibration of handheld drill using accelerometer placed at certain points of the hand drill. Through experiment, the obtained data was analyzed using Fast Fourier Transform (FFT) and Operational deflection shape (ODS) technique and the data being verify which gives the natural frequency at 476.07Hz which is 5.7% higher that theoretical value. From the data the PID controller is designed and tunes using Ziegler Nichols method which gives peak amplitude at 0.0144 and settling time at 0.45s. From the result it is believed that this proposed controller can reduce the vibration and give good improvement to the handheld tool performance.